Perspectives On Lhc Physics - Kane, Gordon; Pierce, Aaron (World Scientific Publishing Company, 2008)
The Large Hadron Collider (LHC), located at CERN, Geneva, Switzerland, is the world's largest and highest energy and highest intensity particle accelerator. Here is a timely book with several perspectives on the hoped-for discoveries from the LHC.This book provides an overview on the techniques that will be crucial for finding new physics at the LHC, as well as perspectives on the importance and implications of the discoveries. Among the accomplished contributors to this book are leaders and visionaries in the field of particle physics beyond the Standard Model, including two Nobel Laureates (Steven Weinberg and Frank Wilczek), and presumably some future Nobel Laureates, plus top younger theorists and experimenters. With its blend of popular and technical contents, the book will have wide appeal, not only to physical scientists but also to those in related fields.